Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3892/etm.2015.2778
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of human amniotic epithelial cell transplantation in treating stage III pressure ulcer in a rat model

Abstract: The aim of the present study was to determine the function of human amniotic epithelial cell transplantation (hAECT) in promoting the healing of rats with stage III pressure ulcer (PU) and to initially investigate its possible mechanisms. A total of 96 Sprague Dawley rats were allocated at random into the model, hAECT, conventional treatment or control groups (n=24 per group). In each group, 6 rats were observed to determine the wound-healing rate. The mRNA and protein expression levels of vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…hAESCs also possess therapeutic capability for wound healing through facilitating migration and proliferation of keratinocytes [ 171 ] and increasing cellularity and re-epithelialization with a paracrine mechanism, which might be mediated by ERK, JNK and AKT signaling pathways [ 172 ]. Zhou et al reported that hAESCs significantly improved the wound healing by upregulating the proangiogenic factor VEGF and downregulating the inflammatory cytokine TNF-α [ 173 ]. hAESCs-derived exosomes promoted the migration and proliferation of fibroblasts and accelerated wound healing, which might be related with stimulating the expression of MMP-1 [ 174 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…hAESCs also possess therapeutic capability for wound healing through facilitating migration and proliferation of keratinocytes [ 171 ] and increasing cellularity and re-epithelialization with a paracrine mechanism, which might be mediated by ERK, JNK and AKT signaling pathways [ 172 ]. Zhou et al reported that hAESCs significantly improved the wound healing by upregulating the proangiogenic factor VEGF and downregulating the inflammatory cytokine TNF-α [ 173 ]. hAESCs-derived exosomes promoted the migration and proliferation of fibroblasts and accelerated wound healing, which might be related with stimulating the expression of MMP-1 [ 174 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%